Salmonella gastroenteritis in children - Yurdakök, Kadriye; Abo Asaker, Esmat A. E.; Berkman, Erdoğan (The Turkish Journal of Pediatrics, 1998)
Among 20,100 children with gastroenteritis admitted to Hacettepe University İhsan Doğramacı Children’s Hospital Diarrhea Training and Treatment Unit between April 1987 and December 1994, 508 Salmonella strains were isolated. Epidemiology, clinical pictures, laboratory findings, and outcome of these patients are discussed. Salmonella gastroenteritis represented 2.5 percent of all diarrheal cases during the study period. The highest number of isolations of Salmonella strains were reported between June and October. Salmonella serogroup B was the most common isolated strain (77%) followed by serogroup D (21%) and serogroup C (2%). Progressive decrease among group B isolations were noted between 1991-1994 with a concomitant increase in group D isolations. S. typhimurium was the most common serotype and overall represented 52 percent of the strains. Bloody diarrhea was found to be present in 27 percent of all cases. It is noted that the patients infected with group B strains had a higher rate of bloody diarrhea than the patients infected with group D strains (30% versus 15%, p < 0.05). Dehydration was present in 14 percent of the cases. We noted that severe dehydration (0.2%) and electrolyte disturbances (1.5%) were rare among our patients. none of the cases had a complication or an extraintestinal manifestation of Salmonella gastroenteritis. No deaths were reported.